2003
DOI: 10.1021/la034667l
|View full text |Cite
|
Sign up to set email alerts
|

Surface Polymerization and Precipitation Polymerization of Aniline in the Presence of Sodium Tungstate

Abstract: Conducting polyaniline films are spontaneously produced on surfaces immersed in the aqueous reaction mixture used for the oxidation of aniline. When a small amount of sodium tungstate, 0.5−5 mol % relative to aniline, is added into the medium, the induction period of the reaction becomes several times longer and the precipitation polymerization is delayed. The surface polymerization of aniline, which precedes the precipitation mode, then produces thicker polyaniline films. The morphology of the films changes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…10.6). It is important to underline that the concept of surface polymerization implies that polymeric organic films are produced on the surface before polymerization in the solution bulk has started (Sapurina et al 2003). However, further experiments are needed to define the reaction sequence at solid/solution interface leading to humic polymers formation.…”
Section: Synthesis Of Humic Substances On the Solution/solid Interfacementioning
confidence: 99%
“…10.6). It is important to underline that the concept of surface polymerization implies that polymeric organic films are produced on the surface before polymerization in the solution bulk has started (Sapurina et al 2003). However, further experiments are needed to define the reaction sequence at solid/solution interface leading to humic polymers formation.…”
Section: Synthesis Of Humic Substances On the Solution/solid Interfacementioning
confidence: 99%
“…In order to verify our mechanism, sodium tungstate was used to elongate the polymerization induction time. [30,31] When 0.060 mmol/ 10 ml sodium tungstate was added into the aqueous solution, the obtained product is a mixture of particles, nanofibers, and little nanosheets as shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results [3,4] indicated that two processes dominate in the in situ polymerization of aniline, adsorption (surface) polymerization and precipitation, the latter that occurs in the bulk phase; adsorption by a film growing on a solid substrate is a fast process taking place after a period of induction, which varies according to solutions, substrates, and temperatures used during the synthesis [3]. In our case, we expect that ultra thin PANI films are formed on the substrate surfaces 20 and 25 min after starting the polymerization reaction.…”
Section: Absorbing Films On a Transparent Glassmentioning
confidence: 93%
“…Recent reports [1][2][3][4][5][6] about how thin films of a conjugated, conducting polymer, polyaniline (PANI), are adherent and conductive when deposited on inorganic particles, textiles and a variety of solid substrates, such as transparent glass and flexible poly(ethylene terephthalate), broadens its applicability on sensors and electronic devices. A common method of preparation of these PANI films is by immersing a solid substrate in the reaction medium containing both monomer and oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation